2018
DOI: 10.1016/j.bpj.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cholesterol Level Alter Integrin Sequestration in Raft-Mimicking Lipid Mixtures

Abstract: The influence of cholesterol (CHOL) level on integrin sequestration in raft-mimicking lipid mixtures forming coexisting liquid-ordered (l) and liquid-disordered (l) lipid domains is investigated using complementary, single-molecule-sensitive, confocal detection methods. Systematic analysis of membrane protein distribution in such a model membrane environment demonstrates that variation of CHOL level has a profound influence on l-l sequestration of integrins, thereby exhibiting overall l preference in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Both are important T-cell markers that are responsible for the localization of T-cells to the colon [ 19 , 28 ]. It has been shown that different integrins are localized into lipid rafts [ 29 ]. As is the case for the TCR signaling, the membrane structure might be important for these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Both are important T-cell markers that are responsible for the localization of T-cells to the colon [ 19 , 28 ]. It has been shown that different integrins are localized into lipid rafts [ 29 ]. As is the case for the TCR signaling, the membrane structure might be important for these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The integrin family of heterodimeric type 1 transmembrane proteins that facilitate the adhesion of cells to the extra‐cellular matrix (ECM) and to other cells is a prime example of one such regulator 50,51 . Experiments from various groups have demonstrated that the sites of integrin activation such as focal adhesions are associated with membranes with an lo ‐like characteristic 52–54 . Cell detachment resulted in the decrease in membrane order suggesting that integrin ECM attachment regulates this process 55…”
Section: Regulation Of Membrane Domains By “Active” Membrane Moleculesmentioning
confidence: 99%
“…Integrin sequestration changes are also dependent on cholesterol concentrations in lipid rafts [ 113 ]. Ligands and bilayer asymmetry influence the sequestering of integrin into rafts and suggest a role of lipid packing and bilayer thickness that characterize the liquid-ordered and liquid-disordered domains in integrin sequestering.…”
Section: The Role Of Cholesterolmentioning
confidence: 99%
“…Recent data showed that systematic changes in the membrane cholesterol concentration impact the sequestration of integrin αVβ3 in coexisting liquid-ordered and liquid-disordered domains, thus being qualitatively distinct in sequestering in the absence and presence of its native ligand vitronectin [ 113 ]. Nevertheless, the role of cholesterol in integrin sequestration and recruitment during lipid membrane raft-mediated integrin signaling and adhesions remains poorly understood, perhaps partly due to the small size and transient nature of raft domains [ 22 , 114 ].…”
Section: The Role Of Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation